(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In today’s interconnected world, where every organization needs a security policy since treats exist not only from outside but also inside an organization. An organizations data security, needs total effort to create, implement, support, and improve the security is called a security program. The success of any security program depends on Good documentation, proper risk assessment and full support from all the employees in the organization. The infrastructure that needs to be in place to achieve organizational security. This topic discusses some of the critical tasks, about development implementation and management of organisational security.